The impact of EFL learners’ perceived teacher emotions on learning engagement: the mediating role of achievement emotions - Shi, Hong; Liu, Ruoxi (Frontiers in Education, 2025)
This study aims to investigate the influence of English major undergraduates’ perceptions of their teachers’ emotions on their learning engagement, while also examining the mediating role of achievement emotions in this relationship. Data were collected from 180 English major undergraduates through a questionnaire survey. Descriptive statistical analyses, correlation analyses, regression analyses, and mediation effect analyses were conducted using SPSS and SPSSPRO. The results revealed that perceived teacher enthusiasm is significantly and positively correlated with student engagement, whereas no significant correlation was found between teacher anger/anxiety and student engagement. Furthermore, foreign language enjoyment, boredom, and anxiety partially mediate the relationship between perceived teacher enthusiasm and student engagement. These findings have important implications for English major teaching practices, highlighting the crucial role of both teacher emotions and students’ achievement emotions in language teaching. We also suggest potential directions for future research.